2021
DOI: 10.3390/ijerph18041757
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Positivity and Passion in Young Mexican Athletes: The Mediating Effect of Social Support

Abstract: The burnout syndrome is a negative experience for athlete development and it has been demonstrated that it gets worse when a sport is practiced in an obsessive way. Interventions with a positive view towards sports could be a protective factor to boost the athlete’s wellbeing. The aim of the present study was to analyse the mediator effect from social support, the relationship between the burnout, positivity and passion in young Mexican athletes. The sample was composed by 452 Mexican athletes, males and femal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The aim of this research is to find out the influence of social support from teammates on futsal athlete burnout and which aspects of social support have the most greater role on preventing athlete burnout. In line with the research by (Martínez-Alvarado et al, 2021), social support has a direct influence on athlete burnout. With the findings in this research, sports players can emphasize that social support and a positive environment are important factors for athletes to maintain athlete performance on and off the field.…”
Section: Associations Between Perceived Social Support From Teammates...supporting
confidence: 82%
“…The aim of this research is to find out the influence of social support from teammates on futsal athlete burnout and which aspects of social support have the most greater role on preventing athlete burnout. In line with the research by (Martínez-Alvarado et al, 2021), social support has a direct influence on athlete burnout. With the findings in this research, sports players can emphasize that social support and a positive environment are important factors for athletes to maintain athlete performance on and off the field.…”
Section: Associations Between Perceived Social Support From Teammates...supporting
confidence: 82%
“…However, according to Schellenberg et al [53], individuals with obsessive passion have low self-identity because they perform tasks regardless of their own will, such as SPP, and show many negative emotions, such as stress. Martínez-Alvarado et al [54] examined the relationship between passion and burnout in young athletes and discovered that harmonious passion decreased burnout and obsessive passion increased burnout.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found in the sample of undergraduates that the general tendency to do prosocial behavior positively correlated with positivity (Laguna et al, 2022). Another study conducted on forty-five young Mexican athletes showed that positivity had a direct and indirect effect through social support toward burnout (Martínez-Alvarado et al, 2021). In a sample of business students in Vietnam, positivity was found to be positively correlated with the quality of college life (Tho et al, 2020).…”
Section: Introductionmentioning
confidence: 91%